Objection in the Administrative Procedure - Milkov, Dragan; Radošević, Ratko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
An objection is a new legal remedy, regulated by the new Law on General Administrative Procedure. Unlike other legal remedies, the objection cannot be used against an administrative act. It can be used against other acts of the administration, to which exercise, formally, the Law on General Administrative Procedure should also apply. In this paper, the authors deal with the legal nature of the objection, trying to determine if the objection can be regarded as a legal remedy at all.